Premium calculation in a heterogeneous portfolio of policies - Pacáková, Viera; Boháčová, Hana (Kalkulacja składki w heterogenicznych portfelach polis, 2010)
The calculation of fair premiums is the main actuarial problem in insurance business. We assume a heterogeneous portfolio of policies such as motor insurance portfolio. The concept of a mixture distribution will be convenient to use and show that the Poisson model for the number of claims and the gamma distribution for the modelling insurance losses are useful in such a case. For a high-volume class of business such as private motor insurance, which has well established rating factors, one of the most common pricing techniques used is generalized li-near modelling. This paper deals with technical aspects of this approach and presents its application for estimating the net premiums according to the rating factors across a group of policyholders
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 106, s. 119-126